2005
DOI: 10.1128/jcm.43.12.6126-6129.2005
|View full text |Cite
|
Sign up to set email alerts
|

Noroviruses as a Cause of Traveler's Diarrhea among Students from the United States Visiting Mexico

Abstract: Stool specimens from 124 international travelers with acute diarrhea were tested for the presence of enteropathogens. Noroviruses (NoVs) were the second most commonly identified enteric pathogen in diarrheal stool samples (21/124, 17%), exceeded only by enterotoxigenic Escherichia coli (50/106, 47%). This study indicates that NoV is an underappreciated cause of traveler's diarrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
45
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 24 publications
9
45
0
Order By: Relevance
“…Travelers who acquired diarrhea in Mexico in 2007 had more NoV GI than GII strains identified, although there were relatively few NoV diarrhea cases in Mexico during this time period. Similarly, in a previous surveillance study performed by our group in Mexico during the summer of 2004, 81% of NoVs detected were NoV GI strains (16). In the present study, 66.7% and 83.3% of NoVs identified in travelers to Mexico in 2002 to 2003 and 2006, respectively, were GII strains.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Travelers who acquired diarrhea in Mexico in 2007 had more NoV GI than GII strains identified, although there were relatively few NoV diarrhea cases in Mexico during this time period. Similarly, in a previous surveillance study performed by our group in Mexico during the summer of 2004, 81% of NoVs detected were NoV GI strains (16). In the present study, 66.7% and 83.3% of NoVs identified in travelers to Mexico in 2002 to 2003 and 2006, respectively, were GII strains.…”
Section: Discussionsupporting
confidence: 52%
“…The two reports demonstrated significant but variable prevalence rates of NoV diarrhea of 17% and 65% in persons visiting Mexico or Mexico and Guatemala, respectively. Interestingly, both studies identified GI NoVs as the genogroup most frequently detected (7,16). The present study was designed to compare patterns of prevalence of NoV infection in international travelers with diarrhea acquired in Mexico over several time periods and in different developing regions of the world, including Mexico, Guatemala, and India, and to characterize the symptoms associated with NoV diarrhea.…”
mentioning
confidence: 99%
“…Ko et al [47] found evidence of norovirus gastroenteritis in 21 out of 124 (17%) US travelers to Mexico. If one considers that up to 40% of traveler's diarrhea is not bacterial or protozoal and that 20% of traveler's symptoms do not respond to antibiotic prophylaxis, this may be the range of frequency of norovirus as a cause of traveler's diarrhea.…”
Section: Travel To Developing Countriesmentioning
confidence: 98%
“…ETEC isolates from travelers can produce heat-labile toxin (LT), heat-stable toxin (ST), or both toxins simultaneously (LT/ST). Approximately 43% to 68% of strains isolated from subjects with TD in Mexico produce LT alone or in combination with ST (1,11,13). Contact with ETEC LT, as a result of vaccination or after natural infection, is associated with the production of LTspecific antibodies (8, 15) and may serve as an indicator of ETEC LT exposure.…”
Section: Up To 60% Of Us Visitors To Mexico Develop Traveler's Diarmentioning
confidence: 99%